Factors Influencing Women’s Career Development (A Case Study of Female Workers in Bali Province) - AMANDA S, E. S. Ghea; KOMALASARI, Yeyen; SANTOSO, R Tri Priyono Budi; I Wayan Ruspendi JUNAEDI (PT. Keberlanjutan Strategis Indonesia, 2024)
Purpose:The research objectives are to identify the factors influencing women's career development, especially in Bali, and determine which factors dominate their career development on the island.Methodology:This research employs a quantitative approach with a survey method to collect data from women holding high positions in companies or institutions in Bali Province. The instrument used for data collection is a questionnaire containing questions related to factors influencing women's career development. Data analysis in this study utilizes factor analysis. The research sample consists of 130 married women with at least one child holding high positions in Bali Province companies or institutions.Findings:The research on the factors influencing women's career development in Bali reveals three key factors. First, the Career Development factor highlights the importance of career position changes in women's careers in Bali. Second, the Career Values & Influences factor emphasizes the importance of personal compromise in women's careers. Third, the Success Perspective factor underscores the sacrifices and benefits of success in women's careers.Implication:The research findings indicate the need to focus on career development and understanding personal values to achieve career success for women, especially in Bali.